The effect of biofertilizers at different levels of moisture stress on the growth and productivity of maize (Zea mays) plants. - ناصيف, احمد; ياسر حماد ,; جهاد ابراهيم ,; مجد درويش, (Latakia University Journal -Biological Sciences Series, 2024)
The research was carried out in the village of Al-Hanadi in Latakia Governorate during the year 2021, by planting yellow corn grains (Ghouta 82) in experimental plots according to a randomized complete block design (RCBD) and with three replicates, with the aim of studying the effect of adding biofertilizers on some growth and productivity characteristics of yellow corn plants. Two types of fertilizers (B1, B2) and a third fertilizer (B3) were used by mixing the previous two types, in addition to a control treatment (C) at three levels of moisture tension (400, 800, 1200) mbar. It was found that when moisture tension (water stress) increased to levels (800) mbar and (1200) mbar, plant productivity decreased. While biofertilizers improved the growth and productivity characteristics of yellow corn plants, giving the highest average plant height of (182 cm), leaf surface area (5084 cm2) number of rows per ear (14.8 rows per ear), and number of grains per row (27.22 grains per row). ), and plant productivity (7.8) tons/ha, in addition to its role in the plant’s tolerance to moisture stress, as it gave an average plant height at level 3Ѱ of (135 cm) compared to the control, which gave a plant height of (90.8 cm), and productivity amounted to (6.35 tons/ha). compared to the control that gave a productivity of (5.2 tons/ha) at the same level of moisture tension. Accordingly, it can be suggested to use biofertilizers due to their tangible role in the plant’s tolerance to moisture stress, in addition to their role in stimulating growth and productivity in yellow maize plants (Ghouta 82